2018
DOI: 10.1002/mrm.27561
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into in‐vivo diffusion tensor cardiovascular magnetic resonance using computational modelling and a histology‐based virtual microstructure

Abstract: Purpose To develop histology‐informed simulations of diffusion tensor cardiovascular magnetic resonance (DT‐CMR) for typical in‐vivo pulse sequences and determine their sensitivity to changes in extra‐cellular space (ECS) and other microstructural parameters. Methods We synthesised the DT‐CMR signal from Monte Carlo random walk simulations. The virtual tissue was based on porcine histology. The cells were thickened and then shrunk to modify ECS. We also created idealise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 68 publications
3
27
0
Order By: Relevance
“…In the ex vivo measurements, it was noted that the MDs increased by 2% and 10%, respectively (baseline) for first‐ and second‐order gradient moment compensation compared to SE‐M0, which was also found in simulations of the SE‐M0 and SE‐M2 gradient waveforms . Detailed data analysis revealed that this increase is primarily driven by increased measured diffusivity along the secondary and tertiary eigenvectors, whereas diffusivity along the primary eigenvector agreed well.…”
Section: Discussionsupporting
confidence: 52%
“…In the ex vivo measurements, it was noted that the MDs increased by 2% and 10%, respectively (baseline) for first‐ and second‐order gradient moment compensation compared to SE‐M0, which was also found in simulations of the SE‐M0 and SE‐M2 gradient waveforms . Detailed data analysis revealed that this increase is primarily driven by increased measured diffusivity along the secondary and tertiary eigenvectors, whereas diffusivity along the primary eigenvector agreed well.…”
Section: Discussionsupporting
confidence: 52%
“…This has been reported before both in vivo and ex vivo [3,12,28]. The higher MD and lower FA values obtained using M2-SE reflect the shorter diffusion time and, therefore, fewer interactions between water molecules and microstructural barriers as demonstrated in recent simulation work [29]. Whilst these differences between sequences were only statistically significant for systole in this study, the trend was present in diastole and lack of statistical significance may reflect the small numbers in this group.…”
Section: Discussionsupporting
confidence: 77%
“…STEAM sequences accommodate longer diffusion times, but also necessitate more complex simulations of the sequence because the magnetization does not remain solely in the transverse plane. Here, we use a simplified version of the STEAM sequence that ignores relaxation effects . If relaxation is ignored in the PGSE sequence, then it also reduces to this simplified STEAM sequence, so we refer to the latter as a generalized diffusion‐weighted sequence.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we use a simplified version of the STEAM sequence that ignores relaxation effects. 21 If relaxation is ignored in the PGSE sequence, then it also reduces to this simplified STEAM sequence, so we refer to the latter as a generalized diffusion-weighted sequence. This generalized sequence allows a wider range of diffusion times, and is introduced here to examine the effect of longer diffusion times on the sensitivity analysis.…”
Section: Pulse Sequence Parameterizationmentioning
confidence: 99%